Patient satisfaction with primary care office-based buprenorphine/naloxone treatment. - Barry, Declan T; Moore, Brent A; Pantalon, Michael V; Chawarski, Marek C; Sullivan, Lynn E; O'Connor, Patrick G; Schottenfeld, Richard S; Fiellin, David A (Journal of general internal medicine, 2007)
Factors associated with satisfaction among patients receiving primary care-based buprenorphine/naloxone are unknown.
Keywords: Adult; Buprenorphine; Female; Humans; Male; Middle Aged; Naloxone; Office Visits; Opioid-Related Disorders; Patient Satisfaction; Primary Health Care; Treatment Outcome